Research on Java card security - Xue-lian ZHANG; Zhen WU; Zhi-bo DU; Min WANG; Chun-ling XIANG (网络与信息安全学报)
To protect privacy and the safety of property,the security research of Java card was proposed.On the basis of systematically discussing the basic composition of Java card,the key of attacking methods were summarized,including logical attack,fault injection and combined attack.At the same time,some problems with the attack process were presented.Moreover,some corresponding countermeasures were put forward and their shortages were analyzed.Finally,the future research direction was prospected.